221 Paraaortic lymphadenectomy in cervical cancer stage IIIC1r international federation of gynecology and obstetrics 2018: experience at the instituto nacional de cancerología. (13th November 2020) - Acosta, J; Rodriguez, J; Velasquez, J; Buitrago, L; Forero, O; Peralta, J; Saenz, J
Abstract : Introduction: The objective of this study is to describe surgical and oncological outcomes of patients with cervical cancer stage IIIC1r FIGO 2018, underwent to staging paraaortic lymphadenectomy at the Instituto Nacional de Cancerología. Bogotá-Colombia, between January 2016 to March 2019. Methods: Retrospective study. Data collected included clinical characteristics, histopathological, surgical results. Furthermore, overall survival and disease-free survival were described in the population. A univariate descriptive analysis was performed. Survival curves were estimated with the Kaplan-Meier method. Statistical software R -Project version 3.6.2 was used. Results: 40 patients were included in the analysis. The mean age was 43 years (29–66). Surgical approach was extraperitoneal in 31 (77.5%) and transperitoneal in 9 (22.5%) of the cases. The mean operating time was 147.5 minutes (120.2 –186.2). Surgical bleeding had a median of 30 ml (10–50). There were no intraoperative complications or death associated with the procedure. The median paraaortic lymph node count was 8.5 nodes (5.75–15). Six (15%) patients had para-aortic compromise and all received extended field radiotherapy. At follow-up, 5% of patients presented recurrent disease (n= 1 lung and n= 1 supraclavicular lymph node). The overall survival (OS) was 88.7% and the disease-free survival (DFS) was 74.3% in the population. Conclusion: Paraaortic lymphadenectomy in stage IIIC1r cervical cancer in our study detected 15% of patients with lymph node involvement, without associated morbidity. It was not possible to evaluate the oncological impact of this procedure in the study population.